A clinic-based tablet application to support safer conception among HIV serodiscordant couples in Kenya: feasibility and acceptability study - Velloza, Jennifer; Ngure, Kenneth; Kiptinness, Catherine; Quame-Amaglo, Justice; Thuo, Nicholas; Dew, Kristin; Kimani, Mary; Gakuo, Stephen; Unger, Jennifer A.; Kolko, Beth; Baeten, Jared M.; Celum, Connie; et al. (mHealth, 2019)
Background: HIV serodiscordant couples are at heightened risk of HIV transmission when attempting to conceive, yet reproductive goals can outweigh concerns about HIV exposure. Safer conception strategies support fertility desires while minimizing HIV transmission risk and novel mHealth tools can optimize their use. The objective of this analysis is to examine the feasibility and usability of short message service (SMS) messages and a mobile application to support safer conception for HIV serodiscordant couples. Methods: We enrolled 74 heterosexual HIV serodiscordant couples with immediate pregnancy desires into a pilot safer conception intervention study in Thika, Kenya. Prior to pregnancy, women received daily 6-item SMS surveys to capture fertility indicators (e.g., menses, basal body temperature) and sexual behavior. The intervention also provided daily oral pre-exposure prophylaxis (PrEP) for the HIV-negative partner and in-depth counseling to accompany publicly-provided antiretroviral therapy (ART) for the HIV-infected partner. Couples attended monthly visits until pregnancy occurred. We measured PrEP use with medication event monitoring system (MEMS) caps and ART use via quarterly viral load quantification. We imported SMS, MEMS, and viral load data into an Android tablet application designed specifically for this setting for couples to view during clinic visits and included predictions of peak fertility days using SMS data. We used descriptive statistics to summarize SMS response data and developed a Google Analytics platform to monitor tablet application usage during follow-up. We also conducted semi-structured interviews with a purposive sample of 5 healthcare providers and 19 couples. Qualitative data were analyzed using a modified constant comparative approach to identify themes related to mHealth intervention feasibility and acceptability. Results: In our sample, 34 (45.9%) couples had an HIV-infected female partner. The median age of the female partner was 30 years [interquartile range (IQR), 27–35 years], education was 10 years (IQR, 8–12 years), and partnership duration was 3 years (IQR, 2–7 years). Couples were followed for a median of 218 days (IQR, 116–348 days) prior to pregnancy. Participants completed 13,181 of 16,905 (78.0%) SMS surveys surveys sent with a median of 167 completed surveys (IQR, 74–299) per participant. Most participants completed at least 75% of the total SMS messages received (N=58; 77.3%). The tablet application was opened by counselors 1,806 times during the study period (March 2016 through April 2018). In qualitative interviews, the SMS messages were reportedly easy to respond to and “part of the daily routine”. Few participants had concerns about message confidentiality. mHealth tools were also found to be acceptable for tracking fertility indicators and enhancing provider-patient communication. Conclusions: mHealth strategies are feasible to use and acceptable to support the delivery of safer conception intervention services among HIV serodiscordant couples in Kenya.